Avaliação da efetividade dos medicamentos modificadores do curso de doença biológicos para o tratamento de espondilite anquilosante no Sistema Único de Saúde. - Bárbara Rodrigues Alvernaz dos Santos (2023)
Introduction: Ankylosing spondylitis (AS) is the main subtype of spondyloarthritis and preferentially affects the axial skeleton. AS affects adults and young people, with a peak incidence in men between 20 and 30 years of age. In the Brazilian Health Public System, the biological disease-modifying drugs (DMARDs) adalimumab, etanercept, infliximab, golimumab, certolizumab pegol, and secukinumab are available as therapeutic options and are indicated as an alternative after failure with the use of non-steroidal anti-inflammatory drugs, glucocorticoids, and synthetic DMARDs. Access to biological DMARDs in the Brazilian Health Public System is through the Specialized Component of Pharmaceutical Assistance and is regulated by the AS Clinical Guideline. In order to access the medication, the doctor and the patient must open an administrative process and complete the Report for Request, Evaluation, and Authorization of Medications (LME) and attach the requested documents. After compliance analysis, the process can be approved, returned, or rejected. Objective: To evaluate the effectiveness of biological DMARDs used in the treatment of AS by patients whose medication request was granted by the Specialized Component of Pharmaceutical Assistance, in Minas Gerais (MG). Methods: This is an open cohort of patients diagnosed with AS, built from data available in the LME and laboratory tests attached to the administrative processes for requesting medication at the Specialized Component of Pharmaceutical Assistance, MG. Patients with the first prescription of biological DMARDs given between June 2018 and December 2021 were included. Demographic, clinical, laboratory data, disease activity and information on adverse reactions, when available, were collected. The time of use, without interruption, of each medication was collected. The causes of interruption of use, due to change or discontinuation, were analyzed. Descriptive analysis was performed using frequency distribution for categorical variables and measures of central tendency for continuous variables. Analysis of variance was used to compare the mean persistence time between biological DMARDs. To compare the proportions of switching, discontinuation and persistence at 6 and 12 months among biological DMARDs, Pearson's chi-square test was used. To assess the independent association between demographic and clinical variables with persistence in treatment, multivariate analysis was performed using the logistic regression model. Results: Of the 456 patients followed up, 52.4% were men, with a mean age of 45.2 years and a mean time since diagnosis of 6.5 years. Of the total, 93.9% had sacroiliitis and 73.2% were positive for the HLA-B27 antigen. Adalimumab was prescribed to 37.7% of patients as the first line of treatment with biological DMARDs, while etanercept was the anti-TNF with the lowest frequency of prescription (5.0%). Fifty-one patients discontinued therapy and 74 switched medications. Patients using etanercept had a higher incidence of switching (30.4%) and discontinuation (17.4%). In the multivariate analysis, the presence of the HLA-B27 antigen and the duration of the disease did not demonstrate a persistent association, as well the biological DMARDs. Conclusion: This was the largest cohort in the state of Minas Gerais that followed patients with AS using biological DMARDs. Through this work, we reinforce the importance of real-world evidence for an adequate assessment of the performance of technologies based on data available in the Brazilian Health Public System. Through the results of treatment persistence, it was identified that biological DMARDs are effective for the treatment of AS. These results are useful for understanding the treatment and the predictors of effectiveness, helping to guide the therapy accordingly.